ArtistRank - an Analysis for the Brazilian Phonographic Scenario - Faria, Felipe Lopes de Melo; Paiva, Débora Maria Barroso; Pereira Jr., Álvaro R. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2017)
The phonographic scenario has changed the way of measuring the artist's popularity. The measurement of an artist's popularity by selling discs or plays on radios was replaced by the artist's dissemination in digital media. Magazines such as Billboard and Rolling Stone build artists rankings, and we may observe that, despite producing many different results, they are accepted in the phonographic scenario. However, they do not have a totally open methodology. In this context, this work aims to apply a methodology for the construction of rankings of artists considering data coming from digital media and TV in the national phonographic scenario. We concluded that the methodology presents satisfactory results and important insights, consistent with the reality of the Brazilian phonographic scenario.